Does utilization of heart machine perfusion for donation after cardiac death transplantation affect outcomes of other abdominal transplanted organs?. Issue 9 (23rd June 2022) - Okumura, Kenji; Misawa, Ryosuke; Ohira, Suguru; Dhand, Abhay; Kai, Masashi; Sogawa, Hiroshi; Veillette, Gregory; John, Devon; Diflo, Thomas; Nishida, Seigo
Abstract: Introduction: Machine perfusion of heart for donation after circulatory death (DCD) is being increasingly utilized. Current protocols for utilizing heart DCD's machine perfusion might prolong donor warm ischemic time for nonheart organs. The aim of this study was to analyze the effects of utilizing heart machine perfusion on liver and kidney transplants from the same donor. Methods: We analyzed data of DCD donors from the United Network for Organ Sharing (UNOS) from January‐2020 to September‐2021 among two groups: donors with heart machine perfusion (HM) and without heart machine perfusion (NHM). Propensity score (PS) matching was performed to compare the short‐term outcomes of liver and kidney transplants between two groups. Results: Total of 102 liver and 319 kidney transplants were performed using organs from donors with HM. After PS matching, no statistically significant difference was seen in 1‐year graft survival (GS) for both liver and kidney transplants between two groups (liver HM 90.6% vs. NHM 90.2%, p = .47; kidney HM 95.2% vs. NHM 92.9%, p = .40). There was no difference in the delayed graft function (DGF) rates in kidney transplantation (KT) (HM 42% vs. NHM 35%, p = .062). Conclusion: Utilization of heart machine perfusion in DCD donors had no significant impact on 1‐year outcomes of liver and kidney transplantation.